Optimizing invasive species management using mathematical programming to support stewardship of water and carbon-based ecosystem services. (1st January 2022) - Pascual, Adrián; Giardina, Christian P.; Povak, Nicholas A.; Hessburg, Paul F.; Heider, Chris; Salminen, Ed; Asner, Gregory P.
Abstract: Invasive species alter hydrologic processes at watershed scales, with impacts to biodiversity and the supporting ecosystem services. This effect is aggravated by climate change. Here, we integrated modelled hydrologic data, remote sensing products, climate data, and linear mixed integer optimization (MIP) to identify stewardship actions across space and time that can reduce the impact of invasive species. The study area is the windward coast of Hawai'i Island (USA) across which non-native strawberry guava occurrence varies from extremely dense stands in lower watershed reaches, to low densities in upper watershed forests. We focused on the removal of strawberry guava, an invader that exerts significant impacts on watershed condition. MIP analyses spatially optimized the assignment of effective management actions to increase water yield, generate revenue from enhanced freshwater services, and income from removed biomass. The hydrological benefit of removing guava, often marginal when considered in isolation, was financially quantified, and single- and multiobjective MIP formulations were then developed over a 10-year planning horizon. Optimization resulted in $2.27 million USD benefit over the planning horizon using a payment-for-ecosystem-services scheme. That value jumped to $4.67 million when allowing work schedules with overnight camping to reduce costs. Pareto frontiers of weighted pairs of management goals showed the benefit of clustering treatments over space and time to improve financial efficiency. Values of improved land-water natural capital using payment-for-ecosystem-services schemes are provided for several combinations of spatial, temporal, economical, and ecosystem services flows. Highlights: We optimized stewardship actions to maximize ecosystem services. Invasive species, forest carbon and water ES are integrated using PES. Clustering drivers supported the multi-temporal scheduling of actions. We applied Pareto optimization to understand synergies and trade-offs. Valuation of land-water natural capital using PES and its temporal benefits.